RESEARCH OF COMPOSITE POLYMER MATERIALS - Xusniddinov Faxriddin Shamsiddinovich (Web of Journals Publishing, 2024)
It is known that many fillers, including kaolin, make it possible to reduce the consumption of binding materials and reduce the cost of plastic, while at the same time the mechanical strength and some dielectric characteristics of composites can increase. The scientific concept has also been known since the early 70s, according to which fillers, usually mechanically mixed with other components, do not enter into chemical interaction with them.
Keywords: reflection, refraction, waves, magnetic structure, electromagnets.